PENGEMBANGAN MODIFIKASI MENU DENGAN PENERAPAN GIZI SEIMBANG TERHADAP STATUS GIZI (IMT/U) REMAJA PESANTREN DI JAKARTA SELATAN - Faiza Camila (2023)
The implementation of a balanced diet through the improvement of menu modifications plays a significant role in adolescent nutrition status optimization. This study aims to develop menu modifications through the implementation of a balanced diet. Furthermore, this study aims to find out the relationship between daily intake (energy, protein, fat, carbs, and fiber) and nutrition status (BMI/A) of adolescents in boarding schools. The design of this research is a Mixed Method of quantitative and experimental. The subjects are 25 and were obtained using the quota sampling method. This study had 15 semi-panelists and 25 untrained panelists. The daily intake data was obtained by 2x24h food recall while the nutrition status data was acquired from the direct measurement of height and weight. Next, the modified menu of a balanced diet was adjusted according to the respondents' questionnaire results of the ingredients' preferences. The result of this study shows that there is a relationship between daily energy intake (p-value = 0,05), daily protein intake (p-value = 0,005), and daily fat intake (p-value = 0,018) with the adolescent's nutrition status (BMI/A). Moreover, there is no relationship between daily carbs intake (p-value = 0,188) with the adolescent's nutrition status (BMI/A). It is to be noted that every fiber consumption of adolescents is under the Recommended Dietary Allowance (p-value = a).